The Impact of the Merdeka Belajar-Kampus Merdeka (MBKM) Program in Improving Student Competence - Wulandari, Novita; Suranto; Wijayanti, Sari; Untari, Ida; Kailani, Ahmad; Rafidiyah, Dina (Jurnal Ilmiah Kampus Mengajar, 2023)
One of the objectives of the MBKM program is to improve the competence of hard skills and soft skills of students. This study aims to determine the impact of the MBKM program in improving student competencies. This research uses a qualitative method with a case study design. The subjects of this study were UMS Accounting Education students class of 2019 and 2020 who participated in the MBKM program and Accounting Education lecturers. The object of this research is the MBKM program and the impact of the MBKM learning program on improving the competence of UMS Accounting Education students. Data collection techniques using interviews and documentation. Data validity techniques used are source triangulation and technique triangulation. Data analysis techniques by means of data reduction, data presentation, and conclusion drawing. The results of this study indicate that students and lecturers are aware of the MBKM program. Before the MBKM program, UMS Accounting Education already had programs similar to MBKM. Students and lecturers who participate in the MBKM program argue that this MBKM program can improve soft skills and hard skills, as well as competencies as a provision for students for life after graduating from college, and can increase the capacity and competence of lecturers. Thus, the MBKM program is expected to produce competitive graduates.